Using QGIS as an Ideal Workspace for Archaeogeography: A Case Study on Castronovo di Sicilia - Gabriele Ciccone (Proceedings)
During the Ph.D. project titled Flying off-site: new investigation methodologies for the analysis of historical landscapes, QGIS was used as a workspace for the archaeogeographical analysis of the territory of Castronovo di Sicilia (PA). The interaction between native applications and plug-ins developed by third parties showed that this software is the ideal environment for a complete archaeogeographical analysis, as it can integrate archaeological and geographical information of different types. The possibility of using a single software not only reduces research costs and time but also allows for new data to be obtained and a holistic approach to be applied to analyzed landscape